Evaluasi Korosi Disk Gate Valve Drain TCA PLTGU Priok - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Ari Fajar Nahor (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
The drain TCA gate valve disk in Unit 3 of PLTGU Priok experienced material degradation dominated by corrosion. This study evaluates the influence of working-fluid temperature and pressure on disk damage using visual observation, metallographic testing, SEM-EDX characterization, Vickers hardness testing, operating-parameter calculation, and fishbone analysis. The investigated disk material was stainless steel SUS316. Metallographic observations showed ferrite and pearlite phases, local voids, and indications of decarburization near the grain boundary. SEM-EDX analysis identified C, N, O, and Fe with weight fractions of 6.87%, 0.50%, 0.72%, and 91.90%, respectively. The average hardness of the used disk was 192 HV, equivalent to about 190 HB and 92 HRB, while comparison with new disk data indicated a significant hardness reduction. Operating analysis showed that pressure increased from 16.57 bar to 18.23 bar and temperature increased from 464.8 deg C to 485 deg C when damage risk became critical. These results indicate that high pressure and temperature accelerate corrosion reactions, reduce material resistance, and shorten valve service life. Strict monitoring of pressure, temperature, cooling effectiveness, and material condition is therefore required